2021
DOI: 10.1038/s41591-021-01464-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of heterologous ChAdOx1 nCoV-19/mRNA vaccination

Abstract: Heterologous priming with the ChAdOx1 nCoV-19 vector vaccine followed by boosting with a messenger RNA vaccine (BNT162b2 or mRNA-1273) is currently recommended in Germany, although data on immunogenicity and reactogenicity are not available. In this observational study we show that, in healthy adult individuals (n = 96), the heterologous vaccine regimen induced spike-specific IgG, neutralizing antibodies and spike-specific CD4 T cells, the levels of which which were significantly higher than after homologous v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

45
339
5
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(393 citation statements)
references
References 19 publications
45
339
5
4
Order By: Relevance
“…In addition, the participants dosed with ChAd-mRNA demonstrate a greater number of circulating spike protein-specific CD4 + and CD8 + T cells, as well as cytokine-producing T cells, than that of participants dosed with ChAd-ChAd. Schmidt et al further demonstrate comparable multifunctional, spike proteinspecific CD4 + T cell responses but greater CD8 + T cell responses in the ChAd-mRNA group 3 . A third study, published recently in Lancet, provides additional evidence that the heterologous ChAd-mRNA vaccine approach is well tolerated and stimulates a robust IgG and neutralizing-antibody response 4 .…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, the participants dosed with ChAd-mRNA demonstrate a greater number of circulating spike protein-specific CD4 + and CD8 + T cells, as well as cytokine-producing T cells, than that of participants dosed with ChAd-ChAd. Schmidt et al further demonstrate comparable multifunctional, spike proteinspecific CD4 + T cell responses but greater CD8 + T cell responses in the ChAd-mRNA group 3 . A third study, published recently in Lancet, provides additional evidence that the heterologous ChAd-mRNA vaccine approach is well tolerated and stimulates a robust IgG and neutralizing-antibody response 4 .…”
mentioning
confidence: 88%
“…These neutralizing titers were approximately threefold higher than those in serum from the groups dosed with BNT-BNT (albeit with differing intervals between dose 1 and dose 2), with higher titers of the IgG and IgA subclasses. Similarly, Schmidt et al show significantly higher titers of IgG antibodies directed against the SARS-CoV-2 spike protein and receptor-binding domain after ChAd-mRNA (either BNT162b2 or mRNA-1273) or mRNA-mRNA vaccination than after homologous ChAd-ChAd vaccination 3 . In addition, the participants dosed with ChAd-mRNA demonstrate a greater number of circulating spike protein-specific CD4 + and CD8 + T cells, as well as cytokine-producing T cells, than that of participants dosed with ChAd-ChAd.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that a second vaccination with BNT was associated with increased anti-spike IgG levels for ChAdOx1-S-primed peopled compared to those having only one ChAdOx1-S dose [10][11][12]. However, contradictory anti-spike IgG levels were observed between participants who received homologous BNT/BNT vaccines or heterologous ChAdOx1-S/BNT vaccines with similar rates [10,13] and higher rates for heterologous ChAdOx1-S/BNT vaccines [9,14,15]. Nevertheless, no evidence of immune response outcomes with heterologous vaccine strategies is clearly available to date for the COVID-19 pandemic [16].…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, on 15 March 2021, numerous European countries stopped ChAdOx1-S vaccine use as a precaution to investigate the death of a few dozen patients developing blood clots associated with deep vein thrombosis (DVT) [3]. In Europe, on 15 March 2021, only 30 suspect cases of DVT had been observed [4]. However, on 22 March 2021, the ChAdOx1-S vaccine campaign resumed in many countries, including France [5].…”
Section: Introductionmentioning
confidence: 99%